Evaluation of Academic Information System Using COBIT 2019 at Universitas Dinami ka Bangsa Jambi: Evaluation of Academic Information System Using COBIT 2019 at Universitas Dinami ka Bangsa Jambi - Beni Irawan; Sirly Aulia Ashar; Amroni (Media Journal of General Computer Science, 2026)
The Academic Information System, commonly known as SIAKAD, played an important role in supporting the implementation of academic processes in higher education institutions, including the management of student information, course scheduling, and grade management. Universitas Dinamika Bangsa Jambi adopted SIAKAD as the primary platform for technology-based academic services. However, in its operation, several issues were encountered, including service availability disruptions, inadequate application responsiveness, and suboptimal management of information technology operations. This situation highlighted the need to assess IT service governance to ensure that the system operated effectively and efficiently. The objective of this study was to evaluate the governance capability of the Academic Information System using the COBIT 2019 framework, particularly within the Deliver, Service, and Support (DSS) domain, focusing on the DSS01 (Manage Operations) and DSS02 (Manage Service Requests and Incidents) processes. The research methodology consisted of observations, interviews, and the distribution of questionnaires to stakeholders identified through the RACI diagram. The data were analyzed using the COBIT 2019 capability level framework in conjunction with the Guttman scale. The findings indicated that the capability level of IT service management fell within the category of a defined process; however, it had not yet been adequately assessed and documented. In addition, a gap was identified between the current condition (As-Is) and the expected condition (To-Be). The recommendations derived from this study included the development of standard operating procedures for IT services, the improvement of operational documentation, and the implementation of periodic monitoring of IT services to enhance the quality of the Academic Information System services at Universitas Dinamika Bangsa Jambi.